2008
DOI: 10.1007/s10705-008-9216-9
|View full text |Cite
|
Sign up to set email alerts
|

Residue quality and N fertilizer do not influence aggregate stabilization of C and N in two tropical soils with contrasting texture

Abstract: To address soil fertility decline, additions of organic resources and mineral fertilizers are often integrated in sub-Saharan African agroecosystems. Possible benefits to long-term C and N stabilization from this input management practice are, however, largely unknown. Our objectives were (1) to evaluate the effect of residue quality and mineral N on soil C and N stabilization, (2) to determine how input management and root growth interact to control this stabilization, and (3) to assess how these relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 37 publications
3
35
0
1
Order By: Relevance
“…5). Even within more sensitive soil aggregate fractions, residue quality did not alter C contents (Gentile et al 2008b). The addition of residues increased soil organic C over the control, but contrary to our hypothesis, it was by equivalent amounts regardless of quality.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…5). Even within more sensitive soil aggregate fractions, residue quality did not alter C contents (Gentile et al 2008b). The addition of residues increased soil organic C over the control, but contrary to our hypothesis, it was by equivalent amounts regardless of quality.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, mineral N levels in the subsoil during the 2007 field season clearly show greater N losses from the top 60 cm from the fertilizer and ). Different letters indicate significant treatment differences at P< 0.05 (data adapted from Gentile et al 2008b) Fig. 4 Residue-derived C stabilized in the in the microcosm experiment after 3 months and 1.5 yr incubation following application of different quality residues (3.65 g C kg −1 soil).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These authors attributed the high SOC to higher lignin content of FYM relative to the other residues. However, residue quality was not found to influence C accumulation in aggregates and silt/clay particles in both clayey and loamy sand soils from Kenya treated for 3 years with organic residues (Gentile et al 2008) corresponding to three of the four classes proposed by Palm et al (2001). These authors suggested that soil disturbance, wetting and drying cycles and effects of crop root residues may have overridden the residue quality influence.…”
Section: Soil Organic C and N Accumulation As Affected By Different Qmentioning
confidence: 96%
“…The losses recorded in this region were greater than those reported by Xiong et al (2008) and Gentile et al (2010). In central Kenya, with an average annual rainfall of 1,200 mm and in a soil with 650 g kg -1 of clay, removal of Eucalyptus harvest residues decreased the content of C-rich macroaggregates by 25 % compared to the content in the area where residues were maintained in the field (Epron et al, 2015).…”
Section: Discussionmentioning
confidence: 60%